DETERMINATION OF RHEOLOGICAL PROPERTIES OF POLYMER AND NATURAL ASPHALTS MODIFIED BINDERS AFTER STORAGE STABILITY TEST - Yılmaz, Mehmet; Kök, Baha Vural; Yamaç, Özge Erdoğan (Yıldız Teknik Üniversitesi, 2015)
In this study, the storage stabilities of modified bitumen prepared with additive of styrene-butadiene-styrene (SBS), Iranian Gilsonite (IG) and American Gilsonite (AG) were investigated. The modified bitumen prepared by mixing each additive in three different ratios to B 160/220 bitumen have been subject to storage stability experiment in accordance with the EN 13399 standard in order to determine the effects of the additive materials. Penetration, softening point and rotational viscosimeter experiments have been applied to the samples. Thus, the additive material that is most suitable in terms of storability was tried to be determined. It has been determined that the penetration, softening point and viscosity values of samples acquired from the top part of the tube was greater due to the polymer accumulation at the top part as a result of the penetration softening point and viscosity experiments carried out on samples prepared with SBS following storage stability. In this study, it was determined that natural asphalts are more suited than SBS in terms of storage stability.